Innovation capacity, organisational culture and gender. Issue 3 (14th August 2017) - Cropley, David; Cropley, Arthur
Abstract : Purpose: The purpose of this paper is to examine the impact of gender diversity on organisational capacity for innovation, and explore the factors that affect the relationship between gender diversity and innovation. Design/methodology/approach: The study applies the Innovation Phase Assessment Instrument (a 168-item survey instrument designed to assess an organisation's alignment to six dimensions of human capital innovation inputs) to members of an Australian manufacturing firm, exploring relationships across both gender and work function in the firm. Findings: Initial results suggest a negative relationship between proportion of females in functional areas and capacity for innovation. Further analysis suggests that capacity for innovation among female employees was suppressed by an unfavourable organisational climate (OC). Practical implications: With a trend towards greater gender diversity as a means for improving organisational innovation, managers should be aware of the role that OC plays in assisting innovation. The relationship between gender diversity and innovation is not merely quantitative, but is also qualitative. Simply increasing the number of females in male-dominated firms may not result in improved innovation capacity. Unless the OC of the firm is aligned to what is needed for successful innovation, the benefits of greater gender diversity may not be realised. Originality/value: This study integrates research from the psychology of creativity and innovation with consideration of organisational design and innovation management. The study demonstrates that a highly differentiated analysis of psychological antecedents to innovation can be used to cast new light on the origins of gender and other group differences in firms. The findings add important new knowledge to the arguments in favour of greater gender diversity as a means for improving organisational innovation.